Contextualizing judgements and decisions in child protection practice at the point of first referral - Guido van de Luitgaarden (Journal of Social Intervention: Theory and Practice, 2011)
Contextualizing judgements and decisions in child protection practice at the point of first referral With the rise of Evidence-Based Practice (EBP), an increasing number of prescriptions relating to judgement and decision-making (JDM) in child protection can be observed. By contrast, there are few descriptions, analyses, and theorizations regarding how child protection practitioners actually pass judgements and make decisions. This paper presents an empirical study that was conducted within the framework of a doctoral research project, which draws on Actor-Network Theory (ANT) and is geared towards understanding child protection JDM processes at the point of first referral. On the basis of analysis of the empirical research data, child protection practices and their relations are conceptualized as layered, parallel, and contingent processes: first, by constructing agency roles, mandates and competences; second, by building an actor-network of informers; and third, through service user identity construction. The dynamics of the processes are illustrated with examples from the data generated. Finally, the implications for research and practice are considered in the light of the insights gained in this study. Oordeels- en besluitvorming in de kinderbeschermingspraktijk in de context van het punt van eerste aanmelding. Met de opkomst van Evidence-Based Practice (EBP) is ook het aantal voorschriften met betrekking tot oordeels- en besluitvorming binnen kinderbeschermingssettings toegenomen. Daar staat tegenover dat beschrijvingen, analyses en theorievorming ten aanzien van de daadwerkelijke oordeels- en besluitvormingsprocessen van professionals in het domein van de kinderbescherming, schaars zijn. In dit artikel wordt een empirische studie gepresenteerd, die uitgevoerd is in het kader van een promotietraject. Actor-Network Theory wordt gebruikt om een beter begrip te ontwikkelen van oordeels- en besluitvormingsprocessen op het punt van eerste aanmelding. Op basis van de analyses van de verzamelde onderzoeksdata, worden de bestudeerde kinderbeschermingspraktijken geconceptualiseerd als een proces bestaande uit drie “lagen” van parallelle en onderling afhankelijke processen: het construeren van de rollen, mandaten en bevoegdheden van de organisatie en individuele professionals; het opbouwen van een Actor-Network van informanten; en het construeren van de identiteiten van cliënten. De dynamiek van deze processen wordt geïllustreerd met citaten uit de gegenereerde data. Op basis van de op basis van deze studie ontwikkelde inzichten, worden de implicaties voor onderzoek en praktijk overwogen.